PENERAPAN MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS V1 PADA MATA PELAJARAN AQIDAH AKHLAK DI MADRASAH IBTIDAIYAH MUHAMMADIYAH TELUK KUANTAN - Yuliastini Yuliastini; Bustanur Bustanur; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Applying the learning model in the learning process is a very easy way to achieve learning objectives. In addition, for the success of the learning process it is necessary to pay attention to the learning model used, so that the material delivered is more easily absorbed or captured by students.The learning model used must start from the learning objectives, because the learning model isbasically a plan to achieve the goal.What is the purpose of this study How to 1.Use the application ofAptitude Treatment Interaction learning model in Enhancing Student V1 Learning Performance inMoral Education Subjects in the Gulf of Muhammadiyah Muhammadiyah Bay of Kuantan? 2. Factors Influencing the Application of Aptitude Treatment Interaction Learning Model in Enhancing Student V1 Learning Performance in Moral Education Subjects in the Gulf of MuhammadiyahMuhammadiyah Bay of Kuantan.Based on the analysis of the author's research data The applicationof the Aptitude Treatment Interaction Learning Model in Improving Student Achievement in ClassV1 in the Aqeedah Moral In Madrasah Ibtidaiyah Muhammadiyah Teluk Kuantan, has increased,Starting pre-action percentage 58.8%, cycle I percentage 74% and cycle II increased by a percentage of 81%. Factors affecting the application of the Aptitude Treatment Interaction learning model in Improving Student Achievement in Class V1 in Aqeedah Moral In Madrasah IbtidaiyahMuhammadiyah, Kuantan, namely 1. Student internal factors (personal factors of students) . 2. Environmental factors. Communication factor.